Investigation of Residual Contamination Inside Storage Cabinets: Collection Care Benefits from an Industrial Hygiene Study. Issue 2 (3rd April 2017) - Kaczkowski, Rebecca A.; Makos, Kathryn A.; Hawks, Catharine; Hunt, Michael
Abstract : Closed storage cabinets become the repository for hazardous vapors emitted by collections, deteriorating cabinet construction materials, and/or collection storage materials, especially wood products and many plastics. Cabinet replacement has been a major goal in the collection care program at the Smithsonian's National Museum of Natural History. The museum has targeted over 5000 old storage cabinets with interior wood framing and wooden drawers for disposal or surplus as funding permits. These cabinets had housed, or continued to house, anthropology and vertebrate zoology collections as well as papers, books, and photographic materials. The cabinets and their past or present contents were known to have been subjected to various pesticide treatments, many of which were presumed to have adsorbed onto or absorbed into cabinet interior materials. In order to understand the risk and to best sequence a staged replacement of old cabinets, the museum administration sought the expertise of occupational health and safety specialists to analyze both the cabinet interior environment and the health exposure risks to anyone accessing the cabinets. Forty volatile organic chemicals were detected in parts per billion (ppb) levels within the cabinets, using the USEPA TO-15 Compendium Method. This dataset and the personal exposure monitoring data set collected showed levels that were significantly less than respective Occupational Exposure Levels, suggesting that human health risk in accessing these cabinets was low. However, the identified chemicals suggest a risk to the collections themselves from continued use of the cabinets. Based on the results of this study, the museum was able to prioritize cabinets for replacement.